2021
DOI: 10.3389/fneur.2021.692128
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Predictors for Endovascular Recanalization of Non-acute Occlusion of Internal Carotid Artery Based on 3D T1-SPACE MRI and DSA

Abstract: Objectives: To investigate the predictive factors for successful recanalization based on digital subtraction angiography and three-dimensional T1W sampling perfection with application-optimized contrasts using different flip angle evolutions (3D T1-SPACE) high-resolution magnetic resonance imaging (MRI) signal features.Methods: Consecutive internal carotid artery occlusion cases with ipsilateral ischemic stroke refractory to therapy who visited our institution between February 2017 and August 2020 were retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
5
8
0
Order By: Relevance
“…However, the predictive value of their method has not been validated due to the limited number of surgery cases ( n = 13). In accordance with traditional DSA features like a tapered stump and reversed the flow of ophthalmic artery, we found that occlusions involving the C6 segment or above and nontapered stump on HR-MRI were independent negative predictors for technical success ( 4 , 17 , 19 ), which may be explained by the significantly increased difficulty of guide wire manipulation in patients with these factors. Theoretically, it is difficult to negotiate the wire through the long CICAO due to the variable vessel course, and it easily induces pseudoaneurysm formation and artery dissection.…”
Section: Discussionsupporting
confidence: 85%
“…However, the predictive value of their method has not been validated due to the limited number of surgery cases ( n = 13). In accordance with traditional DSA features like a tapered stump and reversed the flow of ophthalmic artery, we found that occlusions involving the C6 segment or above and nontapered stump on HR-MRI were independent negative predictors for technical success ( 4 , 17 , 19 ), which may be explained by the significantly increased difficulty of guide wire manipulation in patients with these factors. Theoretically, it is difficult to negotiate the wire through the long CICAO due to the variable vessel course, and it easily induces pseudoaneurysm formation and artery dissection.…”
Section: Discussionsupporting
confidence: 85%
“…However, few studies have investigated the effects of occlusion duration on the technical success of endovascualr recanalization in patients with symptomatic nonacute ILAO. Several recent studies on endovascualr recanalization for nonacute ILAO showed that patients with successful recanalization had a shorter occlusion time, suggesting that the occlusion duration may be associated with technical success [ 11 , 24 , 26 ], but this association was not found in other studies [ 22 ]. These inconsistencies may be partly attributable to the difficulty and inherent limitations of estimating the duration of occlusion from clinical information.…”
Section: Discussionmentioning
confidence: 99%
“…Our technical success and periprocedural complication rates were comparable to those in recently reported case series [ 7 , 8 , 12 , 13 , 18 23 , 26 ]. The technical success and periprocedural complication rates for endovascular recanalization of nonacute ILAO have been reported to range from 53.1 to 100% and 4-44.4%, respectively [ 9 13 , 15 , 17 21 , 23 , 24 ], while the 30-day stroke and mortality rate has been reported to be 3.8-16.7% [ 11 , 18 21 , 23 ]. The differences in the successful recanalization and periprocedural complication rates in these studies may be due to differences in operator experience, intracranial occlusion location, occluded segment characteristics, the interval from vessel occlusion to endovascualr recanalization, and the roadmap techniques used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important point to note is that while it is relatively easy to differentiate ACICAO from dissection, it is often difficult to differentiate ACICAO from chronic carotid artery occlusion. [28][29][30] EVT for chronic carotid artery occlusion is considered technically feasible; however, the risks are fairly high. [31][32][33] In patients with mild symptoms, the possibility of chronic occlusion should be considered and the risks and benefits of intervention with EVT should be carefully assessed.…”
Section: Differentiation From Other Conditionsmentioning
confidence: 99%